2018
DOI: 10.3389/fphar.2018.00300
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic Activity of Ethnomedicinal Xuebijing Revealed by the Metabolomics Analysis Using UHPLC-Q-Orbitrap HRMS

Abstract: Xuebijing (XBJ) injection is an ethnomedicinal formula that has been widely used in the therapy of sepsis in China. However, the underlying theraputic mechanisms remain uninvestigated. In this research, a metabolomic method based on UHPLC-Q-Orbitrap HRMS was applied to make a holistic evaluation of XBJ on septic rats which were induced by the classical cecal ligation and puncture (CLP) operation. The plasma metabolic changes were profiled and evaluated by multivariate analytical (MVA) methods. In the results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that XBJ may protect endothelial cells, improve microcirculation and coagulopathy, attenuate inflammatory reaction and regulate anti-oxidative stress, etc. (Xu et al, 2015;Wang et al, 2016;Chen et al, 2017;Zuo et al, 2018). Although the beneficial effects of XBJ have been widely investigated, the specific molecular mechanisms of XBJ are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that XBJ may protect endothelial cells, improve microcirculation and coagulopathy, attenuate inflammatory reaction and regulate anti-oxidative stress, etc. (Xu et al, 2015;Wang et al, 2016;Chen et al, 2017;Zuo et al, 2018). Although the beneficial effects of XBJ have been widely investigated, the specific molecular mechanisms of XBJ are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The total ion chromatograms in positive and negative ion mode are shown in Figure S1 (supporting information), and all the data were processed with Compound Discoverer 3 to obtain data for the matrix. The analytical samples were normalized with 15 QC samples, in which the missing value of a peak was filled in when the detection rate was >50%, and peaks were excluded when their relative standard deviation in the QC samples was more than 30% 16 . After normalization, 984 and 653 ion peaks were captured in positive and negative ion mode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ultra‐high‐performance liquid chromatography /high‐resolution mass spectrometry (UHPLC/HRMS) has been widely applied in metabolomics 16,17 . In this study we used this technique to monitor changes in metabolites in IFG and T2DM serum samples and to search for an integrated biomarker for diagnosing IFG and T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin (Cas #: 23180-57-6), hydroxysafflor yellow A (Cas#: 78281-02-4), ferulic acid (Cas #:537-98-4), and protocatechualdehyde (Cas#:139-85-5) were purchased from Shanghai Yuanye Biotechnology Co., Ltd. (Shanghai, China). C0127 was prepared with paeoniflorin, hydroxysafflor yellow A, ferulic acid, and protocatechualdehyde according to reported concentrations in XBJ and manufacturer's quality control information (Liu et al, 2015;Zuo et al, 2017;Zuo et al, 2018). The structures of the four compounds in C0127 were presented in Supplementary Figure 1.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Repetitive genes were automatically identified and removed by IPA software. In addition, ingredients derived from XBJ were collected from literature mining (Huang et al, 2011;Jiang et al, 2013;Guo et al, 2014;Han et al, 2017;Zuo et al, 2017;Zuo et al, 2018) and several TCM databases, such as TCMID (Xue et al, 2013) and TCMSP (Ru et al, 2014). Compounds that had more than 10 targets in mammalians were selected for further analysis.…”
Section: Database Construction and Network Analysismentioning
confidence: 99%